2021
DOI: 10.3390/ma14174963
|View full text |Cite
|
Sign up to set email alerts
|

Green and Short Preparation of CeO2 Nanoparticles with Large Specific Surface Area by Spray Pyrolysis

Abstract: Green and short preparation of CeO2 nanoparticles with large specific surface area from rare earth extraction (CeCl3) was successfully achieved by spray pyrolysis (SP). In this method, a precursor solution is first prepared by mixing CeCl3, C6H8O, and H2O in the requisite quantities. Subsequently, the precursor consisting of a mixture of CeO2 and C was obtained by SP method by using the precursor solution. Finally, the calcination at 500 °C~800 °C in air for two hours to transform the precursor to CeO2 nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…15 Cheng et al reported its antioxidant properties using the DPPH radical-scavenging method. 16 Cerium oxide nanoparticles have been synthesized through various methods, including co-precipitation, 17,18 sol-gel, 19,20 microwave combustion, 21 spray pyrolysis, 22 and hydrothermal methods. 23 The hydrothermal method is a simple technique that makes it possible to control the size and morphology of particles.…”
Section: Introductionmentioning
confidence: 99%
“…15 Cheng et al reported its antioxidant properties using the DPPH radical-scavenging method. 16 Cerium oxide nanoparticles have been synthesized through various methods, including co-precipitation, 17,18 sol-gel, 19,20 microwave combustion, 21 spray pyrolysis, 22 and hydrothermal methods. 23 The hydrothermal method is a simple technique that makes it possible to control the size and morphology of particles.…”
Section: Introductionmentioning
confidence: 99%